NUMERICAL ANALYSIS OF AN AHMED BODY WITH DIFFERENT SOFTWARE PACKAGES - Simon Muhič; Matej Štefanič (Journal of Energy Technology, 2024)
In this article, the results of CFD simulations are compared using two different software packages for numerical fluid dynamics. The analysis is performed for an Ahmed body, for which the measurement results and a variety of numerical simulations are available in the literature. The results of the stationary CFD simulations with the RANS approach show a significant difference between the results obtained with the SolidWorks Flow Simulation 2014 software and ANSYS Fluent 16.2 software in the air flow analysis area from 10 m/s to 60 m/s. The difference in computational time is also apparent.